Underpinnings of Islamic Economics Banking and Finance - Awais, Muhammad; Bhatti, Omar Khalid; Yumuşak, İbrahim Güran; Yumuşak, İbrahim Güran (Aurap Publications, 2018)
Do you find yourself unable to understand the basics of Islamic Banking and Finance? Do you need help overcoming the issues regarding Economic System of Islam? Clueless about how modes of Islamic Finance works? This book will give the basic idea regarding the concepts of Islamic Economics, Banking and Finance System. This book “Underpinning of Islamic Economics, Banking and Finance” tells you about the working of Islamic Modes of Financing. On the basis of this book, you will learn that: what The Holy Quran says about the Economic Cycle, how to run the Banking and Finance System according to Shariah, and how to practice Shariah Compliant. We wrote this book to give awareness to the people who really want to know about the working of Shariah Based and Compliant Systems. This book contains: so many Ayaats from the Holy Quran, so many Ahadiths from various well-known books of Hadiths and so many quotations of various Religious scholars to enhance the concepts incorporated in this book. This book have ten sections, involving: Islamic Economic System, Islamic Financing and Banking, Islamic Contracts, Profit and Loss Sharing, Riba, Islamic Investment, Asset-Backed Financing, Islamic Modes of Financing, Special Topics in Islamic Finance and the last one is Differentiate between Islamic and Conventional Banking System.
Keywords: Islamic Economic System; Islamic Financing and Banking; Islamic Contracts; Profit and Loss Sharing; Riba; Islamic Investment; Asset-Backed Financing; Islamic Modes of Financing; Special Topics in Islamic Finance; Islamic and Conventional Banking System